(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
There is no doubt that Mercury is considered one of the significant pollutants to the environment. It have been noticed that exists in three forms. The previously mentioned forms are elementalor metallic (mercury), organic and inorganic mercury. Inorganic mercury can be converted microbiogically into organic form. The present paper has been focused on the genotoxicity and histopathological effect of mercuric chloride on Ctenopharyngodonidella (Grass carp). Basically, Ctenopharyngodonidella is one of the most important fish species according to FAO reports. Moreover, C. idella fry have been divided into four groups. The first Group was exposed to sublethal concentrations of 5 ppb, Second Group was exposed to 10 ppb of mercuric chloride and the third one was exposed to 15 ppb, on the other hand,the fourth Group was kept as unexposed control. Furthermore,A blood smear was done for micronuclei examination and gills and liver of the tested fish were obtained for histopathological study.A significant increase of micronucleus notched erythrocytes in fish exposure with HgCl2 than in the controls). The microscopic examination has shown different histological changes in the organs of the examined fish which has been exposed to mercuric chloride in comparison with control organs.